High-hydrophilic nano-iron-rich polyurethane bio-enriched filler as well as preparation method and application of high-hydrophilic nano-iron-rich polyurethane bio-enriched filler

By preparing highly hydrophilic nano-rich nano-ferrous polyurethane bioenriched filler, the problem of sludge expansion and poor effluent water quality in traditional sewage treatment technology is solved, and more efficient anaerobic ammonia oxidation bacteria enrichment and sewage treatment effects are achieved.

CN119823342AActive Publication Date: 2025-04-15INNER MONGOLIA UNIVERSITY

Patent Information

Application Number
CN202510151997.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-12
Publication Date
2025-04-15
Estimated Expiration
2045-02-12

AI Technical Summary

Technical Problem

Traditional activated sludge treatment technology has defects such as sludge expansion, low activated sludge concentration, easy foam generation, and poor effluent water quality. The existing polyurethane foam filler preparation methods cannot impart the filler specific functions to improve the richness of the specific bacterial population.

Method used

Highly hydrophilic nano-ferrous polyurethane bioenriched filler is used, which includes components such as liquefied starch alcohol, polyether polyol, isocyanate and nano-ferrous powder, and is prepared through liquefaction reaction, mixing and foaming, to improve the hydrophilicity and bioenrichment ability of the filler.

Benefits of technology

The filler has good hydrophilicity and specificity, and can better adsorb and enrich anaerobic ammonia oxidizing bacteria, withstand large load shocks, are not easy to block, improve sewage treatment efficiency and ensure stable operation of the system.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119823342A_ABST
    Figure CN119823342A_ABST
Patent Text Reader

Abstract

The invention provides a high-hydrophilic nano-iron-rich polyurethane bio-enriched filler as well as a preparation method and application thereof, and belongs to the technical field of polyurethane foam fillers. The high-hydrophilic nano-iron-rich polyurethane bio-enriched filler provided by the invention is prepared from the following components in parts by mass: 50 to 70 parts of liquefied starch alcohol, a component A, a component B and 0.2 to 0.3 part of nano-iron powder, wherein the component A is prepared from 130 to 150 parts of polyether polyol, 8 to 10 parts of a foaming agent, 0.7 to 0.9 part of a foam stabilizer and 0.1 to 0.3 part of a gel catalyst; and the component B comprises the following components in parts by weight: 123-125 parts of isocyanate and 0.1-0.3 part of a catalyst. The high-hydrophilic nano-iron-rich polyurethane bio-enrichment filler provided by the invention has good hydrophilicity and specificity, can better adsorb and enrich anaerobic ammonium oxidation bacteria, can bear larger load impact, is not easy to block, and improves the treatment efficiency while ensuring the stable operation of a treatment system.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polyurethane foam fillers, and in particular relates to a highly hydrophilic nano-iron-rich polyurethane bio-enriched filler and a preparation method and application thereof. Background Art

[0002] In recent years, with the continuous improvement of industrialization and urbanization, the discharge of urban sewage and nitrogen and phosphorus pollutants have continued to increase, leading to the current situation of low COD concentration and eutrophication of water bodies in domestic wastewater. The traditional activated sludge treatment technology commonly used in urban sewage treatment has defects such as sludge bulking, low activated sludge concentration, easy foaming, and poor effluent quality. Therefore, in the previous sewage treatment plant denitrification and phosphorus removal upgrading and transformation projects, suspended filler biofilm was often introduced into the original traditional activated sludge biological denitrification system to increase the biomass and improve the volumetric efficiency of the reaction tank.

[0003] As a new type of biofilm carrier, polyurethane foam filler has excellent porosity and mechanical properties. It can not only promote the attachment and film formation of microorganisms, but also has the function of intercepting suspended solids and improving gas-water distribution, thereby improving the effect of sewage treatment.

[0004] At present, the preparation of polyurethane foam fillers for sewage treatment usually adopts a one-step method, such as the patent with application number CN202210054983. However, the above method only prepares hydrophilic cleaning fillers and cannot give the fillers specific functions to increase the richness of specific bacterial flora. Summary of the invention

[0005] In view of this, the purpose of the present invention is to provide a highly hydrophilic nano-iron-rich polyurethane bio-enrichment filler and a preparation method and application thereof. The highly hydrophilic nano-iron-rich polyurethane bio-enrichment filler provided by the present invention has good hydrophilicity and specificity, can better adsorb and enrich anaerobic ammonia-oxidizing bacteria, withstands large load impact, is not easy to clog, ensures the stable operation of the treatment system, and thus improves the treatment efficiency.

[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions: The present invention provides a highly hydrophilic nano-iron-rich polyurethane bioaccumulation filler, which is prepared by the following components in parts by weight: 50-70 parts of liquefied starch alcohol, component A, component B, and 0.2-0.3 parts of nano-iron powder; Component A includes: 130-150 parts of polyether polyol, 8-10 parts of foaming agent, 0.7-0.9 parts of foam stabilizer, and 0.1-0.3 parts of gel catalyst; Component B includes: 123-125 parts of isocyanate and 0.1-0.3 parts of catalyst.

[0007] Preferably, the method for preparing the liquefied starch alcohol comprises: mixing a liquefier, a catalyst and starch, and performing a liquefaction reaction to obtain the liquefied starch alcohol.

[0008] Preferably, the liquefier comprises glycerol and polyethylene glycol, and the mass ratio of the glycerol to the polyethylene glycol is 4:6 to 3:7.

[0009] Preferably, the gel catalyst in component A comprises a triethylenediamine solution.

[0010] Preferably, the foam stabilizer in component A includes L-580, G-580, and W-5903.

[0011] Preferably, the foaming agent in component A comprises water.

[0012] Preferably, the catalyst in the B component includes dibutyltin dilaurate and stannous octoate.

[0013] The present invention also provides a method for preparing the highly hydrophilic nano-iron-rich polyurethane bioaccumulation filler, comprising the following steps: 1) mixing liquefied starch alcohol, component A and nano iron powder to obtain a first mixed solution; 2) mixing the first mixed solution obtained in step 1) with component B to obtain a second mixed solution; 3) The second mixed solution obtained in step 2) is foamed and cured at high temperature to obtain a highly hydrophilic nano-iron-rich polyurethane bio-enriched filler.

[0014] Preferably, in step 3), the foaming temperature is 20-25° C., and the foaming time is 20-40 min; the high-temperature curing temperature is 150-200° C., and the high-temperature curing time is 1-2 h.

[0015] The present invention also provides application of the highly hydrophilic nano-iron-rich polyurethane bio-enrichment filler in sewage treatment.

[0016] Beneficial effects of the present invention: 1. As a new type of biofilm carrier, polyurethane foam filler has excellent porosity and mechanical properties. It can not only promote the attachment and film formation of microorganisms, but also has the functions of intercepting suspended solids and improving gas-water distribution, thereby improving the effect of sewage treatment. The invention adds liquefied starch alcohol to increase the hydroxyl content of the filler, greatly increasing its hydrophilicity, and at the same time has the biodegradable properties of the bioaccumulation filler, becoming an environmentally friendly clean filler.

[0017] 2. Among the many microbial denitrification methods, Anammox technology, as an emerging high-efficiency denitrification technology, not only has high denitrification efficiency and no secondary pollution, but also reduces operating costs. It is of great significance for the treatment of high-ammonia nitrogen wastewater and the alleviation of water eutrophication. Introducing an appropriate amount of iron minerals into the anaerobic ammonium oxidation denitrification system not only helps to promote the enrichment of anaerobic ammonium oxidizing bacteria and iron-reducing bacteria, improve the abundance of functional genes and related enzyme activities, but also may improve sludge performance and improve the stability of the anaerobic ammonium oxidation system by affecting sludge concentration, heme c content, extracellular polymer content and granulation degree. Therefore, in order to obtain a higher denitrification rate and anaerobic ammonium oxidation specific activity, the present invention combines iron powder with a hydrophilic filler to prepare a modified polyurethane foam filler. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 This is a sample picture of the hydrophilic nano-iron-rich polyurethane bioaccumulation filler after biofilm formation prepared in Example 1; Figure 2 This is a sample picture of the hydrophilic nano-iron-rich polyurethane bioaccumulation filler prepared in Example 2 after biofilm formation. DETAILED DESCRIPTION

[0019] The present invention provides a highly hydrophilic nano-iron-rich polyurethane bioaccumulation filler, which is prepared by the following components in parts by weight: 50-70 parts of liquefied starch alcohol, component A, component B, and 0.2-0.3 parts of nano-iron powder; Component A includes: 130-150 parts of polyether polyol, 8-10 parts of foaming agent, 0.7-0.9 parts of foam stabilizer, and 0.1-0.3 parts of gel catalyst; Component B includes: 123-125 parts of isocyanate and 0.1-0.3 parts of catalyst.

[0020] In the present invention, the preparation method of the liquefied starch alcohol preferably comprises: mixing a liquefier, a catalyst and starch, and performing a liquefaction reaction to obtain liquefied starch alcohol. Specifically, the liquefier, the catalyst and starch are mixed, heated and liquefied while stirring, and the temperature change is monitored until the liquefaction reaction is completed to obtain a yellow-brown transparent liquid.

[0021] In the present invention, the liquefier preferably includes glycerol and polyethylene glycol, and the mass ratio of the glycerol to the polyethylene glycol is preferably 4:6 to 3:7.

[0022] In the present invention, the catalyst is preferably a sulfuric acid solution, and the concentration of the sulfuric acid solution is preferably 4% to 8%wt.

[0023] In the present invention, the starch is preferably corn starch, tapioca starch, soluble starch, potato starch; the mass of the starch is preferably 13 to 17 g.

[0024] In the present invention, the heating temperature of the liquefaction reaction is preferably 140-180° C., the stirring speed is preferably 100-120 rm, and the time is preferably 1-2 h.

[0025] In the present invention, the particle size of the nano iron powder is preferably 50-100 nm, and the amount of the nano iron powder added is preferably 0.25-1.25 g. The present invention also provides a method for preparing the highly hydrophilic nano iron-rich polyurethane bioaccumulation filler, comprising the following steps: 1) mixing liquefied starch alcohol, component A and nano iron powder to obtain a first mixed solution; 2) mixing the first mixed solution obtained in step 1) with component B to obtain a second mixed solution; 3) The second mixed solution obtained in step 2) is foamed and cured at high temperature to obtain a highly hydrophilic nano-iron-rich polyurethane bio-enriched filler.

[0026] In the present invention, the component A preferably includes: 130-150 parts of polyether polyol, 8-10 parts of foaming agent, 0.7-0.9 parts of foam stabilizer, and 0.1-0.3 parts of gel catalyst.

[0027] In the present invention, the polyether polyol is preferably 3010, 330N; the gel catalyst is preferably 33% triethylenediamine solution; the foaming agent is preferably water; and the foam stabilizer is preferably L-580, G-580, W-5903.

[0028] In the present invention, the B component preferably includes: 123-125 parts of isocyanate and 0.1-0.3 parts of catalyst.

[0029] In the present invention, the isocyanate preferably includes TDI-80 and TDI-100; the catalyst is preferably dibutyltin dilaurate DBTDL and stannous octoate T-9.

[0030] In the present invention, the amount of the polyether polyol added is preferably 130-150 g, more preferably 140-150 g; the amount of the liquefied starch alcohol added is preferably 52-70 g; the amount of the gel catalyst added is preferably 0.1-0.2 g, more preferably 0.2 g; the amount of the foaming agent added is preferably 5-10 ml, more preferably 9 ml; the amount of the foam stabilizer added is preferably 0.65-0.8 g, more preferably 0.75 g; the amount of the isocyanate added is preferably 115-124 g, more preferably 119 g; the amount of the catalyst added is preferably 0.075-0.200 g.

[0031] In the present invention, the method for mixing the first mixed solution with component B is preferably stirring, the stirring speed is preferably 1000-1500 rm, more preferably 1200 rm, and the stirring time is preferably 5-10 s.

[0032] In the present invention, the low-temperature foaming temperature is preferably 20-25° C., more preferably 23° C.; the low-temperature foaming time is preferably 20-40 min, more preferably 25 min.

[0033] In the present invention, the temperature of the high temperature curing is preferably 150-200°C; the time of the high temperature curing is preferably 1-2h. In the present invention, the preparation method of the highly hydrophilic nano-iron-rich polyurethane bioaccumulation filler preferably specifically comprises the following steps: first, liquefied starch alcohol is prepared, a liquefying agent is mixed with a catalyst and starch, and heated and liquefied while stirring, and the temperature change is monitored until the liquefaction reaction is completed to obtain a yellow-brown transparent liquid; after the liquefied starch alcohol is cooled, it is mixed with the prefabricated A liquid to obtain a primary mixed liquid, and the prefabricated A liquid (A component) and B liquid (B component) are mixed for the second time, and a third mixed liquid is obtained after high-speed stirring, which is quickly sent to a low-temperature foaming chamber for foaming, and high-temperature curing is performed until the foaming is completed to obtain a highly hydrophilic nano-iron-rich polyurethane cleaning foam filler.

[0034] In the present invention, hydrophilicity is usually related to the polar functional groups on the molecular surface, and these functional groups can form stronger hydrogen bonds with water molecules, thereby increasing the hydrophilicity of the molecule. Because liquefied starch alcohol is generated by starch through esterification reaction and alcohols, hydrophilic groups therein may include functional groups such as hydroxyl (-OH) and / or carboxyl (-COOH), because these functional groups have higher polarity, can form hydrogen bonds with water molecules, therefore, selecting it to replace a part of polyether polyol as the raw material of prefabricated A liquid can increase hydrophilicity. Selecting mixed nano iron powder to add in prefabricated A liquid can make it evenly distributed in the whole component inside, nano iron powder and ordinary iron powder have light and easy dispersibility, make iron powder after A liquid and B liquid mixed foaming also can be more easily attached to the network structure of foam, realize specific modification. While adopting high-speed stirring to make the first mixing and the second mixing uniform before foaming, it is also possible to evenly bubble and prevent the bubble size from being different, promote the formation of polymer / gas homogeneous system, promote cell nucleation growth and finalization. The present invention also provides application of the highly hydrophilic nano-iron-rich polyurethane bio-enrichment filler in sewage treatment.

[0035] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention. Example 1

[0036] Raw material preparation: pure water, analytical grade polyethylene glycol, analytical grade glycerol, analytical grade concentrated sulfuric acid, analytical grade soluble starch, purchase of commercial grade 3010 polyether polyol, grade T-9 stannous octoate catalyst, grade A-33 commercial triethylenediamine catalyst, grade W5903 foam stabilizer, grade TDI-80 isocyanate.

[0037] Preparation of liquefied starch: by mass (1g per portion, the same below), first put 100 parts of liquefaction solvent polyethylene glycol and glycerol (7:3) and 3 parts of catalyst (5wt% concentrated sulfuric acid) into a flask and preheat the oil bath to 100°C. Then add 17 parts of starch to the flask and mix thoroughly with the liquefied chemicals. Add starch in batches, continue to heat to 150°C for 4 hours, and continue to stir at normal pressure for liquefaction. After the preset reaction time, turn off the heater and continue stirring until the mixture cools.

[0038] Ingredients: In terms of mass, pour 60 parts of liquefied starch alcohol into measuring cup A, add 140 parts of 3010 polyether polyol and 9 parts of pure water and stir slightly, then use a syringe to extract 0.8 parts of foam stabilizer W5903 and add it. Add 124 parts of isocyanate raw material TDI-80 into measuring cup B. By titration and gravimetric method, 0.2 parts of gel catalyst A33 is 25 drops, and 0.2 parts of catalyst T-9 is 28 drops, which are added to measuring cups A and B respectively, and gently stirred evenly.

[0039] Material mixing and foaming: Weigh 0.25 parts of nano iron powder by mass, add it to measuring cup A, and stir evenly. Quickly pour the liquid in measuring cup B into measuring cup A, use an industrial mechanical stirring arm to stir, adjust the speed to 1500rm, and the stirring time to 8s. Quickly pour the material into the foaming box, send it to the low-temperature foaming room, and adjust the temperature to 23℃.

[0040] Curing: After the foam is cooled, it is demoulded and sent into the oven for high-temperature curing, and the temperature is adjusted to 150℃.

[0041] Foam cutting: Take the foam out of the foaming box, peel it and cut it into 20mm×20mm×20mm squares. The foam porosity after cutting is greater than 95% and the bulk density is 0.047g / cm 3 , put it in running water, and completely immerse it in water after 5 seconds. The stirring or flowing water environment is conducive to faster infiltration of the networked foam. Nano iron powder can be seen on the surface, with a coverage of more than 70%.

[0042] Example 2

[0043] Raw material preparation: pure water, analytical grade polyethylene glycol, analytical grade glycerol, analytical grade concentrated sulfuric acid, analytical grade soluble starch, purchase of commercial grade 3010 polyether polyol, grade T-9 stannous octoate catalyst, grade A-33 commercial triethylenediamine catalyst, grade W580 foam stabilizer, grade TDI-80 isocyanate.

[0044] Preparation of liquefied starch: by mass (1g per portion, the same below), first put 100 parts of liquefaction solvent polyethylene glycol and glycerol (7:3) and 3 parts of catalyst (5wt% concentrated sulfuric acid) into a flask and preheat the oil bath to 100°C. Then add 17 parts of starch to the flask and mix thoroughly with the liquefied chemicals. Add starch in batches, continue to heat to 150°C for 4 hours, and continue to stir at normal pressure for liquefaction. After the preset reaction time, turn off the heater and continue stirring until the mixture cools.

[0045] Ingredients: In terms of mass, pour 52 parts of liquefied starch alcohol into measuring cup A, add 148 parts of 3010 polyether polyol and 9 parts of pure water and stir slightly, then use a syringe to extract 0.8 parts of foam stabilizer W580 and add it. Add 124 parts of isocyanate raw material TDI-80 into measuring cup B. By titration and gravimetric method, 0.2 parts of gel catalyst A33 is 25 drops, and 0.2 parts of catalyst T-9 is 28 drops, which are added to measuring cups A and B respectively, and gently stirred evenly.

[0046] Material mixing and foaming: Weigh 0.15 parts of nano iron powder by mass, add it to measuring cup A, and stir evenly. Quickly pour the liquid in measuring cup B into measuring cup A, use an industrial mechanical stirring arm to stir, adjust the speed to 1500rm, and the stirring time to 8s. Quickly pour the material into the foaming box, send it to the low-temperature foaming room, and adjust the temperature to 23℃.

[0047] Curing: After the foam is cooled, it is demoulded and sent into the oven for high-temperature curing, and the temperature is adjusted to 150℃.

[0048] Foam cutting: Take the foam out of the foaming box, peel it and cut it into 20mm×20mm×20mm squares. The foam porosity after cutting is greater than 90% and the bulk density is 0.035g / cm 3 , put it in running water, and completely immerse it in water after 12 seconds. The stirring or flowing water environment is conducive to the faster infiltration of the networked foam. Nano iron powder can be seen on the surface, with a coverage of more than 60%.

[0049] Example 3

[0050] The hydrophilic nano-iron-rich polyurethane bioaccumulation fillers prepared in Examples 1 and 2 were cut into 20mm*20mm*20mm block fillers, and placed in a 400ml anaerobic bottle with the same volume of a commonly used hydrophilic sponge on the market to inoculate and enrich anaerobic ammonia-oxidizing bacteria for biofilm formation. After biofilm formation, the fillers were taken out and placed in 100ml light-proof anaerobic bottles.

[0051] The simulated nitrogen-containing wastewater is introduced, and the simulated nitrogen-containing wastewater is prepared by sodium nitrite, potassium dihydrogen phosphate, potassium bicarbonate, ammonium chloride and tap water. The nitrite nitrogen concentration in the simulated nitrogen-containing wastewater is 20 mg / L, and the ammonia nitrogen concentration is 15 mg / L. The anaerobic bottle is placed in a shaking table, with a constant temperature of 30 degrees Celsius and a rotation speed of 140rm. The sample picture after 15 days of film formation is as follows. The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, without departing from the principle of the present invention, several improvements and modifications can be made, and these improvements and modifications should also be regarded as the protection scope of the present invention.

Claims

1. A highly hydrophilic nano-iron-rich polyurethane bioaccumulation filler, characterized in that: The method comprises the following components in parts by weight: 50-70 parts of liquefied starch alcohol, component A, component B, and 0.2-0.3 parts of nano iron powder; Component A includes: 130-150 parts of polyether polyol, 8-10 parts of foaming agent, 0.7-0.9 parts of foam stabilizer, and 0.1-0.3 parts of gel catalyst; Component B includes: 123-125 parts of isocyanate and 0.1-0.3 parts of catalyst.

2. A highly hydrophilic nano-iron-rich polyurethane bioaccumulation filler according to claim 1, characterized in that: The preparation method of the liquefied starch alcohol comprises: mixing a liquefier, a catalyst and starch, and performing a liquefaction reaction to obtain the liquefied starch alcohol.

3. A highly hydrophilic nano-iron-rich polyurethane bioaccumulation filler according to claim 2, characterized in that: The liquefier comprises glycerol and polyethylene glycol, and the mass ratio of the glycerol to the polyethylene glycol is 4:6 to 3:

7.

4. A highly hydrophilic nano-iron-rich polyurethane bioaccumulation filler according to claim 1, characterized in that: The gel catalyst in the A component includes a triethylenediamine solution.

5. A highly hydrophilic nano-iron-rich polyurethane bioaccumulation filler according to claim 1, characterized in that: The foam stabilizers in the A component include L-580, G-580 and W-5903.

6. A highly hydrophilic nano-iron-rich polyurethane bioaccumulation filler according to claim 1, characterized in that: The foaming agent in the A component includes water.

7. A highly hydrophilic nano-iron-rich polyurethane bioaccumulation filler according to claim 1, characterized in that: The catalyst in the B component includes dibutyltin dilaurate and stannous octoate.

8. The method for preparing a highly hydrophilic nano-iron-rich polyurethane bioaccumulation filler according to claim 1, characterized in that: The following steps are involved: 1) mixing liquefied starch alcohol, component A and nano iron powder to obtain a first mixed solution; 2) mixing the first mixed solution obtained in step 1) with component B to obtain a second mixed solution; 3) The second mixed solution obtained in step 2) is foamed and cured at high temperature to obtain a highly hydrophilic nano-iron-rich polyurethane bio-enriched filler.

9. The method for preparing a highly hydrophilic nano-iron-rich polyurethane bioaccumulation filler according to claim 8, characterized in that: In the step 3), the foaming temperature is 20-25° C., and the foaming time is 20-40 minutes; the high temperature curing temperature is 150-200° C., and the high temperature curing time is 1-2 hours.

10. Use of the highly hydrophilic nano-iron-rich polyurethane bioaccumulation filler according to claim 1 in sewage treatment.

Citation Information

Patent Citations

  • Conductive polyurethane biological filler and preparation method thereof

    CN113512171A

  • Super-net polyurethane foam filler and preparation method thereof

    CN114380978A

  • Polyurethane structure, soundproof material, method for producing polyurethane structure and liquid composition for forming polyurethane film

    JP2021130265A

Cited By

  • Polyurethane composite material and application thereof

    CN121021795A

  • Polyurethane composite and use thereof

    CN121021795B